2013
DOI: 10.1037/a0027879
|View full text |Cite
|
Sign up to set email alerts
|

Supporting children in U.S. legal proceedings: Descriptive and attitudinal data from a national survey of victim/witness assistants.

Abstract: We conducted a national survey of 786 victim/witness assistants (VWAs) to provide descriptive and attitudinal information about support person use in U.S. legal proceedings involving children. VWAs (N = 414) from 46 states returned completed surveys (response rate = 53%). Prosecutor-based VWAs or parents/guardians most frequently served as support persons. One support person was almost always or often used with child victims and/or witnesses of all ages. Support persons were extremely common in cases involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Participants believed that all forms of alternative testimony would be less stressful for children than testifying live in court. This finding is consistent with the views of judges (Hafemeister, 1996), prosecuting attorneys (Goodman et al, 1999), and victim witness assistants (McAuliff et al, in press) regarding the ability of support persons, CCTV, and videotape to reduce children's stress while testifying. These views also are consistent with the results of experimental and quasi-experimental research comparing children's traditional versus prepared (Sas, 1991; 1993), videotaped (Davies et al, 1995), and CCTV testimony (Cashmore, 1992; Davies & Noon, 1988; Goodman et al, 1998; Landström & Granhag, 2010; Murray, 1995).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Participants believed that all forms of alternative testimony would be less stressful for children than testifying live in court. This finding is consistent with the views of judges (Hafemeister, 1996), prosecuting attorneys (Goodman et al, 1999), and victim witness assistants (McAuliff et al, in press) regarding the ability of support persons, CCTV, and videotape to reduce children's stress while testifying. These views also are consistent with the results of experimental and quasi-experimental research comparing children's traditional versus prepared (Sas, 1991; 1993), videotaped (Davies et al, 1995), and CCTV testimony (Cashmore, 1992; Davies & Noon, 1988; Goodman et al, 1998; Landström & Granhag, 2010; Murray, 1995).…”
Section: Discussionsupporting
confidence: 84%
“…Ninety percent of judges responding to another survey believed that allowing a child to testify on an adult's lap effectively minimized the child's trauma compared to 83% and 79% who felt the same about the use of videotape and CCTV, respectively (Hafemeister, 1996). Victim witness assistants share attorneys' and judges' optimism for the ability of support person use to reduce children's stress, particularly when the support person accompanies the child to trial and provides pretrial preparation (McAuliff, Nicholson, Amarilio, & Ravanshenas, in press). Quasi-experimental work on children in actual trials who provided traditional versus prepared (Sas, 1991; 1993), videotaped (Davies et al, 1995), or CCTV testimony (Cashmore, 1992; Davies & Noon, 1988; Murray, 1995) showed that the vast majority of legal professionals believed the innovations effectively reduced children's stress.…”
Section: Jurors' Beliefs About Alternative Testimony Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…With older children, support persons may continue to help children regulate their emotions, but may do so by teaching children problem-solving and other coping strategies rather than by directly engaging in regulation of the children's emotions. Support person use is becoming increasingly common in legal settings (Goodman et al, 1999 ;Hafemeister, 1996 ;McAuliff, Nicholson, Amarilio, & Ravanshenas, 2013 ), especially in criminal cases. In the USA, for example, both federal and state statutes allow for the appointment of support persons for child witnesses in criminal proceedings.…”
Section: Children's Coping With Legal Involvementmentioning
confidence: 99%